VD_FINDINFO HC / 2012 / 485 vom 14. Juni 2012 - VD Tribunal cantonal (2012)
PROTECTION DE L'UNION CONJUGALE, RÉSIDENCE HABITUELLE | 176 CC, 48 LDIP, 85 al. 1 LDIP, 2 CLaH 96, 3 CLaH 96, 5 CLaH 96, 308 al. 1 let. b CPC (CH)